PEMBELAJARAN MODEL "SPELT" UNTUK MENINGKATKAN HASIL BELAJAR MAHASISWA DALAM MATA KULIAH PSIKOLOGI OLAHRAGA - Dimyati Dimyati (Jurnal Kependidikan, 2006)
Abstract Result learn the student of FIK UNY in subject Sport Psychology less gratifying. Approach model the Strategy Program for Effective Learning/ thinking (SPELT) represent one effort innovate to  increase the quality of result learn the students. This research aim to know the  model applying in improving achievementlearn the student of FIK UNY in subject Sport Psychology. This research use the device of action research. Subject and research object is student FIK UNY. Used Research Instrument: (1) pre test and post test; (2) sheet of method observation learn; and (3) sheet of observation of assessment of student activity in study;(4) sheet of applying observation model the SPELT. Data type obtained by there is two that is quantitative data and qualitative by using technique analysis t test. Result of research indicate that the Sport Psychology study by applying model the SPELT earn: (1) improving result learn the student in subject Sport Psychology; and  (2) increasing the quality of study process in subject Sport psychology. Keywords: SPELT models, sport psychology.